(untitled) (Journal of Nepal Geological Society, 2003)
The landslide hazard zonation of Dharasu-Tehri -Ghansali area of Garhwal Himalaya has been carried out using Indian Remote Sensing (IRS) LISS II and SPOT (MLA) data for various geo-environmental parameters viz. lithology, structure, land use/land cover, slope and drainage. The forest types and density and other land uses in the reservoir rim area were delineated and also assessed the direct loss of forests, agricultural land, wastelands and other landuse in the submergence area of the Tehri dam. There are 71 landslides in the periphery of the Bhagirathi and the Bhilangana rivers, which will enclose the impounded reservoir. Out of 71 landslides 35 will get submerged during the reservoir-filling phase while remaining will continue to exist. By overlaying the thematic maps in Geographical Information System (GIS) environment and using statistical parameters, a landslide hazard zonation map has been prepared. Phyllite, dissected hills, slope 50°-60°, agriculture and convex side of stream channel were to be found more susceptible for landslide. An area of 43.5 km2 in the reservoir rim falls in the category of high to very high class as per the landslide hazard zone code.